Fast and slow components of cerebral blood flow response to step decreases in end-tidal PCO2 in humans. - Poulin, M; Liang, P; Robbins, P (1998)
This study examined the dynamics of the middle cerebral artery (MCA) blood flow response to hypocapnia in humans (n = 6) by using transcranial Doppler ultrasound. In a control protocol, end-tidal PCO2 (PETCO2) was held near eucapnia (1.5 Torr above resting) for 40 min. In a hypocapnic protocol, PETCO2 was held near eucapnia for 10 min, then at 15 Torr below eucapnia for 20 min, and then near eucapnia for 10 min. During both protocols, subjects hyperventilated throughout and PETCO2 and end-tidal PO2 were controlled by using the dynamic end-tidal forcing technique. Beat-by-beat values were calculated for the intensity-weighted mean velocity (VIWM), signal power (P), and their instantaneous product (P.VIWM). A simple model consisting of a delay, gain terms, time constants (tauf,on, tauf, off) and baseline levels of flow for the on- and off-transients, and a gain term (gs) and time constant (taus) for a second slower component was fitted to the hypocapnic protocol. The cerebral blood flow response to hypocapnia was characterized by a significant (P < 0.001) slow progressive adaptation in P.VIWM, with gs = 1.26 %/Torr and taus = 427 s, that persisted throughout the hypocapnic period. Finally, the responses at the onset and relief of hypocapnia were asymmetric (P < 0.001), with tauf,on (6.8 s) faster than tauf,off (14.3 s).